An Investigation in Temperature Data Analysis of Middle Atmospheric Variation from SABER Satellite - E. Raghavendrakumar, V. Kamalakar and K. Sunil Kumar (Nature Environment and Pollution Technology, 2024)
This paper focuses on significant data analysis for middle atmospheric variations of height of 0 km 100 km. This data was downloaded from the SABER satellite NASA and analyzed with the help of MATLAB. The analysis includes the determination of propagation of wavelengths and oscillations for the semi-annual oscillation (SAO), Annual oscillations (AO), quasi-annual oscillations (QBO), EINIO southern oscillation (ENSO) from the period of Jan 2002 to Dec 2022 past twenty years data. The monthly mean Temperatures, monthly ozone deviations, and overall mean temperatures with standard deviations are estimated for the following altitude regions concerning troposphere (0-20km), stratospheric (21-50 km), mesospheric (51-90 km), and thermospheric regions (91-105 km). However, the results proved that the maximum temperature variations would affect the ozone depletion for the areas concerning the altitude height of 15-40 km region between troposphere and stratospheric in the temperature range of 260K, and average deviations are found in the order of 0.000010 μm for the troposphere region. The presence of harmful gases such as CO, CO2, NOx, H, and CH4 released from the automobile and powerplant industry may deplete the ozone layer and cause adverse effects.